THE INFLUENCE OF HALAL LABELING, HALAL AWARENESS, AND INFLUENCERS ON THE PURCHASE INTENTION OF GEN-Z MUSLIM CONSUMERS ON HALAL COSMETIC PRODUCTS IN SURABAYA - Balqis - - (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2025)
The objective of this research is to determine how halal labels, halal awareness, and halal influencers affect Gen-Z Muslim consumers' purchasing intentions for halal cosmetics in Surabaya. The distribution of online questionnaires served as the major data source for this descriptive quantitative study design. There were 100 respondents in all, and the sampling method was carried out using the purposive sampling technique. Multiple linear regression on the SPSS application was used to analyze the data. According to the results of this study, halal awareness and influencers have an impact on Gen-Z Muslim consumers' purchase intentions for halal cosmetic products in Surabaya. Meanwhile, halal labels do not influence Gen-Z Muslim consumers' intentions to purchase halal cosmetic items in Surabaya. Marketers should display the halal logo on the packaging of cosmetic items sold.